Efficiency Centered Maintenance of Preheat Train of a Crude Oil Distillation Unit (2020)
Nowadays, maintenance is based on the synergistic integration of operational reliability and timely maintenance, which guarantees the required availability and optimal cost. Operational reliability implies producing more, better performance, longer life, and availability. Timely maintenance involves the least time out of service, fewer maintenance costs, fewer operating costs, and less money. In this work, we study the preheating train of a crude distillation unit of a refinery, which processes 994 m3/h, which presents a formation of a foulinglayer inside it. Among the impacts of fouling is the reduction in the effectiveness of heat transfer, the increase in fuel consumption, the increase in CO2 emissions, the increase in maintenance costs, and the decrease in the profit margin of process. An appropriate cleaning program of the surface of the heat exchanger network is necessary to preserve its key performance parameters, preferably close to design values. This paper presents the maintenance method centered on energy efficiency, to plan the intervention of the preheating train equipment maintenance, which considers the economic energy improvement and the cost of the type of maintenance. The method requires the calculation of the fouling evolution from which the global heat transfer coefficient is obtained, and the heat flux is determined as a function of time. It was observed that, as time passes, the resistance provided by fouling increases and that the overall heat transfer coefficient decreases. The energy efficiency centered maintenance has an indicator of economic justification (factor J) that relates the economic-energy improvement achieved when performing maintenance, taking into account the economic effort invested. Depending on the cost of the type of maintenance to be performed, a threshold should be chosen, from which the maintenance activity is justified. The effectiveness values of the heat exchanger (e) and the J indicator are used to form a criticality matrix, which allows prioritizing maintenance activities in each equipment. The planning of the implementation dates of the maintenance of each heat exchanger, from the maintenance method centered on energy efficiency applied to the crude distillation unit's, preheat train, constitutes a contribution in this specific field. The conceptual design of the maintenance method centered on energy efficiency presented in this work is feasible for other heat transfer equipment used in oil refineries and industry in general. The procedure developed uses real operation values, and with its implementation, a saving of 150000 US dollars was achieved. © 2020 ASME.